2018
DOI: 10.3390/ijms19061643
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Obestatin—A Ghrelin Gene-Encoded Peptide—Reduces the Severity of Experimental Colitis Evoked by Trinitrobenzene Sulfonic Acid

Abstract: Obestatin is a 23-amino acid peptide derived from proghrelin, a common prohormone for ghrelin and obestatin. Previous studies showed that obestatin exhibited some protective and therapeutic effects in the gut. The aim of our presented study was to examine the effect of treatment with obestatin on trinitrobenzene sulfonic acid (TNBS)-induced colitis. In rats anesthetized with ketamine, colitis was induced through intrarectal administration of 25 mg of 2,4,6-trinitrobenzene sulfonic acid (TNBS). Obestatin was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 99 publications
(142 reference statements)
2
20
0
1
Order By: Relevance
“…Ghrelin administered to animals with dextran sulfate sodium -induced colitis restored both the DNA synthesis, and normal blood flow contributing to the preventive effect against progression of DSS-induced colitis [ 73 ]. Similar results were obtained for obestatin in the case of aceticacid-induced colitis [ 74 ] and trinitrobenzene sulfonic acid (TNBS)-induced colitis [ 75 ]. PPIs were recognized as important dysbiotic medicines increasing susceptibility to Clostridium difficile infection [ 76 ] as well as small intestinal bacterial overgrowth, bacterial peritonitis, and poor outcomes in inflammatory bowel disease [ 77 ].…”
Section: Discussionsupporting
confidence: 77%
“…Ghrelin administered to animals with dextran sulfate sodium -induced colitis restored both the DNA synthesis, and normal blood flow contributing to the preventive effect against progression of DSS-induced colitis [ 73 ]. Similar results were obtained for obestatin in the case of aceticacid-induced colitis [ 74 ] and trinitrobenzene sulfonic acid (TNBS)-induced colitis [ 75 ]. PPIs were recognized as important dysbiotic medicines increasing susceptibility to Clostridium difficile infection [ 76 ] as well as small intestinal bacterial overgrowth, bacterial peritonitis, and poor outcomes in inflammatory bowel disease [ 77 ].…”
Section: Discussionsupporting
confidence: 77%
“…Meanwhile, obestatin, similarly to grelin, exhibited some protective and therapeutic effects in the stomach ulcers and duodenum colitis. With reference to gastric cancer, the obestatin stimulates mitogenesis of gastric cancer cells [ 59 , 60 , 61 , 62 ]. Therefore, further studies utilizing more neuronal markers (especially sensory markers), have to be carried out, in order to elucidate the relevance of different subpopulation of neurons innervating the stomach wall [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The protective or therapeutic effect of obestatin has been observed in the heart [291,292,293], kidney [294] and skeletal muscle [295]. In the gut, animal studies have shown that obestatin accelerates the healing of chronic gastric ulcer evoked by acetic acid [296] (Figure 3), attenuates mesenteric ischemia/reperfusion-induced oxidative injury of the ileum and lung [297], inhibits the development of acetic acid-induced colitis [298], reduces the severity of experimental colitis evoked by trinitrobenzene sulfonic acid [299] and accelerates the healing of acetic acid-induced colitis in rats [300]. In the pancreas, obestatin promotes the survival of pancreatic beta-cells and human islets and induces the expression of genes involved in the regulation of beta-cell mass and function [282], as well as enhances the in vitro generation of pancreatic islets through the regulation of developmental pathways [301].…”
Section: Obestatin and Its Protective And Therapeutic Effectsmentioning
confidence: 99%
“…Previous studies have shown that pretreatment with obestatin inhibits the development of dextran sulfate sodium-induced colitis [226] and acetic acid-induced colitis in rats [298]. The therapeutic effect of obestatin has been found in experimental colitis evoked by acetic acid [300] or trinitrobenzene sulfonic acid [299]. The beneficial effect of obestatin has been also found in the liver, where it exhibits a protective effect against ischemia/reperfusion-induced hepatic injury [306], as well as inhibits and reverses the development of nonalcoholic fatty liver disease [307].…”
Section: Obestatin and Its Protective And Therapeutic Effectsmentioning
confidence: 99%